DAMPAK FISIOLOGIS PENGGENANGAN (WATERLOGGING) PADA TANAMAN - Achmad Fatchul Aziez (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2012)
Flooding is the presence of ground water (or other root media) that exceeds the capacity of the field. There are two physiological effects of flooding include : 1. The primary impact of the stress of water shortages due to a potential decline in water, and 2. Secondary effects of stress that is the gaseous stress and ions stress. Ion stress caused by the loss of mineral nutrients, while the gas stress in plants by flooding, there are three causes of the lack of oxygen, excess carbondioxide and excess ethylene. Lack of oxygen is divided into two, namely a state where no available oxygen is called anoxia, and the circumstances in which oxygen is available but it was not normal is called hypoxia. The presence of oxygen deficiency on rhizosfere will cause damage to the plants growing on it. This damage is caused by a disturbance in metabolic processes such as photosynthesis, respiration, carbohydrate distribution, loss of mycorrizae, interference with absorption of nutrients, hormonal disorders, enzymatic activity, the emergence of toxic anaerobic metabolites that would result in the disruption of plant growth. While the impact of excess carbon dioxide in the state were flooding including the accumulation of toxins such as asetaldehide and ethanol. High concentrations of carbondioksida encourage the activity of catalase, nitrate reductase and glycolate oksidase.